Attention and psychological assistance to minor children victims of gender or domestic violence (art. 72.2 CDFA) - Serrano García, José Antonio (Revista de derecho aragonés, 2022)
Commentary to art. 72.2 CDFA, introduced in 2021, so that the intervention of both parents is not necessary when psychological assistance is due to cases of gender or domestic violence; In such cases, the consent of the other parent will suffice if the children are under fourteen years of age, and the parent who caused the violence must be previously informed. For children over fourteen years of age, the provisions of articles 23 and 24 of the CDFA will be followed. It gives an account of the parliamentary processing of the reform, in which the Aragonese Civil Law Commission intervened, and it is related to the reforms of other Spanish civil rights that have the same foundation.
Keywords: Relations between ancestors and descendants; exercise of family authority; interference in personality rights